2005
DOI: 10.1158/1078-0432.ccr-05-0411
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of CDKN2A Status in Microdissected Urothelial Cell Carcinoma Reveals Potential Haploinsufficiency, a High Frequency of Homozygous Co-deletion and Associations with Clinical Phenotype

Abstract: Purpose: There are significant differences in reported frequencies, modes of inactivation, and clinical significance of CDKN2A in urothelial cell carcinoma (UCC). We aimed to address these issues by investigating all possible modes of inactivation and clinicopathologic variables in a single tumor panel. Experimental Design: Fifty microdissected UCCs were examined. CDKN2A gene dosage (quantitative real-time PCR), allelic status (microsatellite analysis), hypermethylation (methylationspecific PCR), mutation stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
44
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 40 publications
5
44
0
1
Order By: Relevance
“…Iacobucci et al 13 reported that CDKN2A/B deletions had independent significance for lower disease-free survival in a series of 112 adult Ph-positive patients, but other authors did not show any prognostic impact. 27 No differences in outcomes were observed from a comparison of heterozygous and homozygous CDKN2A/B deletions, 12 and this suggests an important haplo-insufficiency effect 28 or concomitant inactivation of the remaining allele by epigenetic events. 29,30 Although our patients were treated within protocols, some limitations should be pointed out.…”
Section: Discussionmentioning
confidence: 94%
“…Iacobucci et al 13 reported that CDKN2A/B deletions had independent significance for lower disease-free survival in a series of 112 adult Ph-positive patients, but other authors did not show any prognostic impact. 27 No differences in outcomes were observed from a comparison of heterozygous and homozygous CDKN2A/B deletions, 12 and this suggests an important haplo-insufficiency effect 28 or concomitant inactivation of the remaining allele by epigenetic events. 29,30 Although our patients were treated within protocols, some limitations should be pointed out.…”
Section: Discussionmentioning
confidence: 94%
“…53 Although P16INK4A deletion has an undisputed role in transitional bladder carcinoma progression, P16INK4A DNA methylation is highly variable between individual bladder carcinoma patients and the contribution of epigenetic factors to bladder carcinoma risk is still controversial. 54,55 UTI-induced CDKN2A methylation could provide a mechanism for the observed correlation between recurrent UTI and bladder carcinoma risk. [56][57][58] After infection, bladder uroepithelial cells undergo apoptosis that results in shedding of infected cells and intracellular pathogens, thereby reducing the overall pathogen load.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional CGH and array-GCH have corroborated many of these findings but have also defined several recurrent high-level amplifications and deletions (3)(4)(5)(6)(7)(8). The key results of these investigations are losses of chromosome 9, or 9p and 9q, frequent amplification of 6p22 (9)(10)(11), and loss of RB1 (12). Apart from chromosomal changes, several genes are known to be mutated in bladder cancer including FGFR3, PIK3CA, KRAS, HRAS, NRAS, TP53, CDKN2A, and TSC1, of which activating mutations in FGFR3 and inactivating mutations in TP53 are the most frequent.…”
Section: Introductionmentioning
confidence: 86%